Association of alexithymia, emotional regulation, and insomnia with alcohol dependence syndrome in a cross-sectional study - Anand Bhogaraju; Yasaswi Kadaru (Telangana Journal of Psychiatry, 2025)
Background: There are few Indian studies on insomnia, emotional dysregulation, and alexithymia in alcohol use disorder (AUD). Aims: The aim is to find the association between alexithymia, insomnia, emotional dysregulation, and the severity of AUD. Methodology: In an ethics committee-approved, cross-sectional study on AUD subjects aged between 18 and 70 were assessed on the Alcohol Use Disorders Identification Test (AUDIT), Athens Insomnia Scale (AIS), Toronto Alexithymia Scale (TAS-20), and Dysfunctional Emotional Regulation Scale-18 (DERS-18). The sample size was calculated. Statistical analysis consisted of data description and Pearson’s correlation. A matrix scatterplot for the variables with the best-fit line was depicted. Results: Twenty-eight (26 males and two females) with a mean age of 40.32 years belonging to lower upper socioeconomic strata formed the sample in the study. AUDIT score mean (21.46) and standard deviation (5.62) fall in the alcohol dependence range (TAS-20). The mean of 59.07 suggests a possible alexithymia. Insomnia was present on (AIS) with a mean score of 8 (DERS-18). The mean score of 36.64 suggests some degree of emotional dysregulation. The severity of alcohol dependence (AUDIT scale) significantly positively correlates with AIS (r = 0.483, P = 0.009) followed by DERS-18 (r = 0.476, P = 0.011) and TAS-20 (r = 0.406, P = 0.032). Conclusions: Our study demonstrated a significant positive relationship between the severity of alcohol use, insomnia, alexithymia, and emotional dysregulation. Emotional issues and insomnia need to be focused in the treatment of AUD.